Pride amid Prejudice: The Influence of LGBT+ Rights Activism in a Socially Conservative Society - AYOUB, PHILLIP M.; PAGE, DOUGLAS; WHITT, SAM (The American political science review, 2021)
How do mass publics react to lesbian, gay, bisexual, and transgender (LGBT+) advocacy efforts in socially conservative societies? We consider how the first-ever LGBT+ Pride in Sarajevo, Bosnia and Herzegovina influences ordinary citizens’ attitudes and behavior regarding LGBT+ support. Using nationwide and local panel surveys, we find that support for LGBT+ activism increased locally after the Pride but did not diffuse nationwide, signaling how proximity mechanisms reinforce Pride effects. In survey experiments, we show that subjects are responsive to both mobilization and counter-mobilization appeals by local activists. We also find evidence from a behavioral experiment that the Pride had a positive effect on shifting the allocation of financial resources toward local pro-LGBT+ activists and away from opposition groups. Finally, in-depth interviews with local LGBT+ activists underscore the challenges facing LGBT+ activism in socially conservative societies but also point to the substantial possibilities of collective action on behalf of minorities at risk.